2015
DOI: 10.3111/13696998.2015.1086775
|View full text |Cite
|
Sign up to set email alerts
|

Cost and co-morbidities associated with hypoglycemic inpatients in Belgium

Abstract: Hospitalizations for hypoglycemia are expensive and associated with an increased risk of depression and traumatic fractures as well as increased in-hospital mortality. Interventions that can help reduce the risk of hypoglycemia, and consequently the burden on hospitals and society, without compromising glycemic control, will help to further improve diabetes management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A proportion of 3% is approximately at the same level as reported by Chevalier et al [26] and Khunti et al [24] but higher than the rates reported by Geller et al [27].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A proportion of 3% is approximately at the same level as reported by Chevalier et al [26] and Khunti et al [24] but higher than the rates reported by Geller et al [27].…”
Section: Discussionsupporting
confidence: 68%
“…Compared with other studies (e.g., Marchesini et al [28], Chevalier et al [26] and Cryer [29]) these death rates are low.…”
Section: Discussionmentioning
confidence: 75%
“…There are many depression assessment scales for the application of diabetes at home and abroad, but unfortunately it has not been used clinically. Therefore, it is recommended that diabetics be able to evaluate depression using a highly reliable and effective depression assessment scale, and I believe there will be benefits for the disease control of diabetes [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…These negative impacts of hyperglycaemia increase risk of falls. Additionally, hypoglycemic that has been reported to increase the risk of falls is more common in OWD (Chevalier et al., 2016; Kachroo et al., 2015). OWD have increased risk of falls because of the simultaneously existing ageing and diabetes.…”
Section: Introductionmentioning
confidence: 99%